2005
DOI: 10.1111/j.1600-051x.2005.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic risk factors for periodontitis and possible mechanisms of action

Abstract: Mutations in the cathepsin C gene (CTSC) have been identified as causal for the Papillon-Lefèvre syndrome (PLS), which includes prepubertal periodontitis (PP). Some CTSC mutations are causal for PP without PLS. No relationship has been demonstrated between CTSC mutations and other forms of periodontitis. Genetic polymorphisms in a candidate gene approach have been explored as risk factors for periodontitis. There is limited evidence that some polymorphisms in the genes encoding interleukins (IL)-1, Fc gamma re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
224
1
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(244 citation statements)
references
References 185 publications
(210 reference statements)
6
224
1
13
Order By: Relevance
“…6 However, most studies showed variable and inconclusive correlations between the presence of the disease and the tested single-nucleotide polymorphisms (SNPs) in both forms of periodontitis. 7 These findings might be consistent with the hypothesis, debated by Moore 8 and Templeton, 9 that epistasis is likely to be a ubiquitous component of the genetic architecture of common human diseases, in general, and AgP in particular. In other words, it may be that the positive results from different studies in terms of the association between of single polymorphisms and AgP do not replicate across independent samples because of epistasis.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…6 However, most studies showed variable and inconclusive correlations between the presence of the disease and the tested single-nucleotide polymorphisms (SNPs) in both forms of periodontitis. 7 These findings might be consistent with the hypothesis, debated by Moore 8 and Templeton, 9 that epistasis is likely to be a ubiquitous component of the genetic architecture of common human diseases, in general, and AgP in particular. In other words, it may be that the positive results from different studies in terms of the association between of single polymorphisms and AgP do not replicate across independent samples because of epistasis.…”
Section: Introductionsupporting
confidence: 85%
“…As complex diseases, such as periodontitis, are typically polygenic, 23 they are associated with variations in multiple genes, each providing a small overall contribution to the disease susceptibility and to the severity of the pathologic process. Similarly to other complex diseases, Loos et al 7 estimated at least 10, and as high as 20, modifying disease genes involved in periodontitis susceptibility. There have been some early attempts to analytically search for epistatic effects in the pathogenetic pathway of periodontitis, 24,25 but some of these genetic effects may be undetectable by current single-locus methodology.…”
Section: Discussionmentioning
confidence: 99%
“…3 While microbial and environmental factors (lifestyle factors [as smoking and stress] or acquired diseases [as diabetes]) characteristically modulate host responses (and consequently periodontitis outcome), studies suggest that as much as 50% of the risk of disease can be determined by genetic factors, [4][5][6] and that numerous disease modifying genes may be involved in the pathogenesis of periodontal diseases by modulating the host's response and his susceptibility to infection. 3,7,8 Recently, the interaction between host genetic factors that can impact the ability of pathogens to invade and proliferate on host's tissues has been termed infectogenomics. 9 This concept highlights the close and intimate dependence of the host's immune mechanisms and the commensal and/or pathogenic microflora, which co-evolved in a mutually dependent fashion.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 gen polimorfizminin periodontitis veya periodontal doku yıkımının şiddeti için risk faktörü olarak tanımlanamaya-cağı ileri sürülmüştür. 44 IL-1 gibi periodontitisin patogenezinde önemli role sahip olan TNF-α'nın gen polimorfizmi ile periodontitis arasındaki ilişkiyi değerlendiren çalışmalara göre TNF-α geninin allel sıklığı da IL-1 gibi farklı etnik toplumlarda çeşitlilik gös-termektedir. TNF-α gen polimorfizmi ile periodontitis arasında ilişki olduğunu belirten çalış-malara 47 karşın, ilişkinin olmadığını ileri süren çalışmalar da [47][48][49][50][70][71][72][73] bulunmaktadır.…”
Section: Peridontal Hastalıkta Genetik Faktörlerin Rolüunclassified